Security in Libraries: Matching Responses to Risks - Gill, Martin (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Security in libraries is a major issue. The need to permit public access and at the same time protect what are often valuable resources can sometimes conflict. In this paper it is argued that it is vital to develop a holistic strategy, and one of the best ways of developing effective responses is to understand how offenders behave and target security resources to counteracting specific threats.